Service Quality Gap Model as a Predictor of Customer Satisfaction among People with Disabilities in Vocational Rehabilitation Centers - Ahmed Natto, Hawazin Mohammed (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
The purpose of this study was to investigate the Service Quality Gap Model as a predictor of customer satisfaction among people with disabilities in Vocational rehabilitation centers. A quantitative survey research method was employed for this study. The independent variable is Service Quality Gap Model, while the dependent variable is customer satisfaction. The data were analyzed with Pearson correlation and multiple regression. Multiple regression was used. Participants were 150 individuals with disabilities (females, n= 10, 6.66%, and males 140, 93.33%). Findings show significant correlations between service quality gap model subscales and customer satisfaction. When put together, the independent variables (tangibility, reliability, responsiveness, assurance, and empathy) yielded a coefficient of multiple regression (R) of 0.664 and a multiple correlation square of 0.621. Each of the five independent variables made significant individual contributions to the prediction of customer satisfaction.